O wielości metod w filozofii Wolffa - Paź, Bogusław (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2012)
The main goal of the article is to demonstrate that (against general opinion) Wolff used not one but few different research methods in his philosophy. Except mathematical (more geometrico), there were semiotic, eidetic and reflective ones. Moreover I indicate the presence of reductive, transcendental, and rhetorical method elements in Wolff's works. Each of this methods are represented in this article in details with an examples of their usage by Wolff. The choice of the methods and the structural relation between them are not coincidental. In the current article I try to prove that the heuristic epistemological primacy in Wolff's philosophy belongs not to the mathematical but to eidetic method. Speaking of the relation type between eidetic method and the rest of them – semiotic, reflective and axiomatic (mathematical one) – I would define it as: (1) genetic dependence, since eidetic method is the reason of existence of the rest of the methods, (2) heuretic dependence, while eidetic one gives the opportunity for the reflection over the rest of the methods, and (3) epistemological dependence, while eidetic method provides criteria of truth (reliability) of the knowledge for the rest of methods.